2005
DOI: 10.1577/t04-115.1
|View full text |Cite
|
Sign up to set email alerts
|

Prey Selectivity and Diet of Striped Bass in Western Albemarle Sound, North Carolina

Abstract: We collected 1,399 striped bass Morone saxatilis from western Albemarle Sound, North Carolina, during May through October of 2002 and 2003 to characterize diet, prey type selectivity, and prey size selectivity. Herrings Alosa spp., Atlantic menhaden Brevoortia tyrannus, bay anchovy Anchoa mitchilli, silversides Menidia spp., and yellow perch Perca flavescens dominated the diets of age-1 striped bass, while Atlantic menhaden dominated the diets of older striped bass. Selectivity was calculated for three categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 35 publications
1
36
1
Order By: Relevance
“…Plots in Walter and Austin (2003), Rudershausen et al (2005), and Overton et al (2009) indicated that 3-year-old Striped Bass were the first ageclass capable of consuming age-1 Atlantic Menhaden. We considered all size-groups of Bluefish capable of consuming age-1 Atlantic Menhaden after examining prey fish length and Bluefish length plots in Scharf et al (2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plots in Walter and Austin (2003), Rudershausen et al (2005), and Overton et al (2009) indicated that 3-year-old Striped Bass were the first ageclass capable of consuming age-1 Atlantic Menhaden. We considered all size-groups of Bluefish capable of consuming age-1 Atlantic Menhaden after examining prey fish length and Bluefish length plots in Scharf et al (2000).…”
Section: Methodsmentioning
confidence: 99%
“…However, diet studies of large Striped Bass by Walter and Austin (2003) and Overton et al (2008) suggested a greater role of Atlantic Menhaden of all ages in Striped Bass diets. Atlantic Menhaden were often dominant prey in studies of Striped Bass diets in the Chesapeake Bay and the midAtlantic region and were important prey in New England waters (Walter and Austin 2003;Rudershausen et al 2005;Nelson et al 2006;Overton et al 2008Overton et al , 2009Overton et al , 2015. After recovery of Atlantic coast Striped Bass was declared in 1995 (Richards and Rago 1999), concern emerged about the impact of the large Striped Bass population size on its prey base, and multiple analyses suggested that the recovered Striped Bass population had the potential to deplete prey populations along the Atlantic coast (Hartman 2003;Hartman and Margraf 2003;Uphoff 2003;ASMFC 2004;Savoy and Crecco 2004;Heimbuch 2008;ASMFC Weakfish Technical Committee 2009;Davis et al 2012).…”
mentioning
confidence: 99%
“…Similarly, Markle and Grant (1970) found that fish occurred in >20% of the stomachs containing food and represented >50% by volume of the diet of juvenile striped bass between 30 and 150 mm TL from three major tributaries in the southern region of Chesapeake Bay. Moreover, striped bass appear to make an even earlier shift to piscivory at more southern latitudes, as age-1 striped bass in the Albemarle Sound estuary, North Carolina, were found to be completely piscivorous (>95% FO and % weight) by June of their second summer during two independent studies separated by more than 30 years (Manooch 1973;Rudershausen et al 2005). Larger body sizes at age-1 for striped bass at southern latitudes (Rudershausen et al 2005) provide a greater size advantage over piscine prey and may be mostly responsible for an earlier shift to a piscivorous diet in these systems.…”
Section: Patterns Of Resource Utilizationmentioning
confidence: 99%
“…Adults spawn in the spring in inshore waters, and their offspring grow rapidly at mid and high latitudes until the young of the year migrate offshore in autumn (Conover and Murawski 1982;Conover and Present 1990). This species is an important prey item for many recreationally and commercially valuable fishes, such as Bluefish Pomatomus saltatrix, Striped Bass Morone saxatilis, and Summer Flounder Paralichthys dentatus (Buckel et al 1999;Manderson et al 2000;Rudershausen et al 2005), and it faces high mortality from both predation and overwinter starvation (Munch et al 2003). Silversides are easily cultured in the laboratory, making it possible to obtain precise estimates of their size distributions through time; daily increment formation has previously been validated (Barkman and Bengtson 1987).…”
Section: Methodsmentioning
confidence: 99%